RELATIONSHIP BETWEEN FAMILY HISTORY, BLOODY STOOL, PALPABLE MASS, ANEMIA, AND MSCT ABDOMEN AND KOLON CARSINOMA Cross-Sectional Study at Dr.Kariadi General Hospital in 2016 - Malik, Ricat Hinaywan; Winarto, Winarto; Budijitno, Selamat; Sadhana, Udadi; Prajoko, Yan Wisnu (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2018)
Background: Colon cancer, a colorectal cancer, is the third most common epithelial malignancy in the world. Family history, bloody stool, palpable mass, anemia, and abdominal MSCT are symptoms and signs of colon carcinoma.Objective: To determine the relationship between the 5 variables and the incidence of colon carcinoma at Dr. Kariadi Hospital, Semarang in 2016.Methods: a Cross-sectional observational analytical study using medical record (RM) and complementary primary data. The inclusion criteria werethe complete medical record, and clinical diagnosis of suspected colon carcinoma. Data obtained from the department of Anatomy Pathology/PA (11,794PA results) were traced to the medical record section (46 patients with suspected colon carcinoma). The incomplete data were confirmed by: contacting the patient/family, obtaining the archive in the laboratory and radiology resulting in 27 patients meeting the inclusion criteria. Analysis was done using chi-square test, Spearman-Kendall bivariate correlation, and logistic regression.Results: Abdominal MSCT was moderately associated with colon carcinoma (p = 0.003; r = 0.488), while family history, bloody stool, palpable mass, and anemia were not associated with colon cancer. Analysis between predictors of outcome: Bloody stool was moderately associated with anemia (p = 0.006; r = 0.411), and anemia was weakly associated MSCT (p = 0.035; r = 0.351). Abdominal MSCT was the predictive factor for colon carcinoma (p = 0.021).Conclusion: Abdominal MSCT was found to be associated with the incidence of colon carcinoma. Bloody stool was associated with anemia, and anemia was associated with abdominal MSCT. MSCT was the predictive factor for colon cancer.